Pushing regional studies beyond its borders. Issue 1 (2nd January 2020) - Harrison, John; Delgado, Mercedes; Derudder, Ben; Anguelovski, Isabelle; Montero, Sergio; Bailey, David; De Propris, Lisa
ABSTRACT: This paper explores how to push the field of regional studies beyond its present institutional, conceptual and methodological borders. It does this from five perspectives: innovation and competitiveness; globalization and urbanization; social and environmental justice; local and regional development; and industrial policy. It argues that the future of regional studies requires approaches that, in combination, result in the pushing on (by creating), pushing off (by consolidating), pushing back (by critiquing) and pushing forward (by collectively constructing) the field.